SOCIAL INNOVATION – THEORY AND PRACTICE FROM THE PERSPECTIVE OF “CREATIVE CITY – SUSTAINABLE REGION” (KRAFT) NATIONAL PROGRAMME - Szabó, Mariann; Galambos, Katalin; Z. Karvalics, László; Jensen, Jody Patricia; Miszlivetz, Ferenc (European Integration Studies, 2022)
In this study we summarize the importance, research aspects of social innovation both from the theoretical and practical points of view. We begin with the introduction of the KRAFT Programme (started in 2012), a pilot regional development policy and its relation to social innovation. It is followed by presenting the interrelatedness of social innovation and the UN Sustainable Development goals, highlighting the various challenges which should be addressed. In accordance with many years of experience in regional development, we put much emphasis on the governance of social innovations and the variety of actors which could be the initiators. In this regard, we describe how different organizations can be engaged in such practices resulting in social change (social meta-innovation). Finally, we highlight some best practices in the field of social innovation at the Institute of Advanced Studies Kőszeg (iASK).